2010
DOI: 10.1159/000258662
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender and Age on Anorectal Function: Normal Values from Anorectal Manometry in a Large Caucasian Population

Abstract: Introduction: In the literature, data on the effects of gender and age on the pressure data of anorectal manometry differ. Possible reasons are investigation of only small numbers of healthy people and comparison of only 2 groups with large age differences. In addition, data about the influence of gender or age on anorectal sensation are sparse. Therefore, the aim of the present study was to determine the influence of gender and age on anorectal manometry in a large healthy female and male cohort spanning a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 81 publications
10
75
3
1
Order By: Relevance
“…The IAS plays a key role in maintaining continence, providing 55% -85% of MRP [3,4]. Several studies have investigated the effect of sex on resting pressure of the anal canal [12][13][14][15]. The data are contradictory, with about half of the studies reporting comparable resting pressures in women and men, and the other half citing lower resting pressure in women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IAS plays a key role in maintaining continence, providing 55% -85% of MRP [3,4]. Several studies have investigated the effect of sex on resting pressure of the anal canal [12][13][14][15]. The data are contradictory, with about half of the studies reporting comparable resting pressures in women and men, and the other half citing lower resting pressure in women.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies observed a significant lowering of MRP with age (more often in women than in men), while others found only a small decrease in MRP that did not reach statistical significance. Other studies did not see a decreased MRP in their older subjects [12][13][14][15]. In addition to the aforementioned problem of small sample size, most studies included patients of varying ages and grouped them differently.…”
Section: Open Accessmentioning
confidence: 99%
“…Manometry assesses the mechanical strength of the anal sphincters (76,77). A range of methods are available, including water perfused, solid state and microballoon systems.…”
Section: Manometrymentioning
confidence: 99%
“…However, age and gender have to be considered when comparing healthy and incontinent people. Mean resting (MRP) and squeeze (MSP) pressure decreases with aging [5]. Furthermore, female sex influences anorectal pressure as well as sensory parameters [5].…”
Section: Introductionmentioning
confidence: 99%